Persistent pulmonary interstitial emphysema presenting as solitary lung cyst in a preterm infant. (14th December 2012) - Srinivasan, Ramesh; Ali, Haytham; Harigopal, Sundeep
Abstract : Solitary unilateral lung cyst is an unusual finding in preterm infants. It may be difficult to distinguish acquired from congenital lung cysts clinically. The definitive diagnosis is histological; however, CT scan of the chest is a useful diagnostic tool. We present an extremely preterm infant with solitary lung cyst and background chronic lung disease. The initial chest x-rays showed solitary right lung cyst. At 6 weeks he required an escalation of ventilator support coupled with x-ray evidence of increased size of the cyst. CT scan confirmed large solitary cyst of the right lower lobe with evidence of compression and mediastinal shift, suspicious of congenital cystic adenomatoid malformation. The cyst was surgically removed in view of clinical deterioration. However, histology showed persistent pulmonary interstitial emphysema (PPIE). This case illustrates that in the context of prematurity PPIE can present as a solitary lung cyst and may require surgery.